Barium sulphate modified fishing gear as a mitigative measure for cetacean incidental mortalities - Trippel, E. A.; Holy , N. L.; Shepherd , T. D. (J. Cetacean Res. Manage., 2023)
Incidental mortality from entanglements in fishing gear is threatening cetacean populations worldwide. In eastern Canadian waters, entanglement deaths of the critically endangered transboundary North Atlantic right whale (Eubalaena glacialis) are a key conservation concern and incidental mortalities of harbour porpoise (Phocoena phocoena) in gillnets are a major source of mortality. Since the 1990s, a number of mitigation techniques to reduce mortalities in both species have been tested and the use of some in the US commercial fishery have been legislated. Despite this, the North Atlantic right whale population remains in a precarious state and entanglement deaths of harbour porpoise have been increasing in recent years. Further, mitigation devices, such as acoustic alarms, carry with them concerns about habituation, noise pollution, maintenance requirements and cost. The modifying of the physical characteristics of commercial fishing gear has shown some promise at reducing entanglement mortalities in initial testing while avoiding many of the drawbacks of other mitigation methods. In this study the current state of development and effectiveness of mitigation techniques through the addition of barium sulphate to fishing gear rope and twine were investigated. The development of a neutrally buoyant groundline, through the addition of barium sulphate, was undertaken in order to reduce the probability of large whale entanglements in lobster pot gear. The resulting product maintained a much lower profile in the water column relative to traditional polypropylene groundline, however, it was found unsuitable for hard-bottom areas as it was susceptible to chaffing and breaking. In order to reduce mortalities once large whales are entangled, a weak rope was developed again with the addition of barium sulphate. The breaking strength of this product was found to be 1,065lb which meets the US legislated limits (1,100lb), as opposed to traditional polypropylene rope which had a breaking strength of over 2,400lb. To meet the challenge of harbour porpoise entanglements, a gillnet twine was developed to have an increased acoustic profile and a more stiff form through the addition of barium sulphate. In field testing trials, the barium sulphate modified gillnets reduced harbour porpoise bycatch and had minimal effects on targeted groundfishes. Although they are in an early state of development, barium sulphate modified fishing gear shows promise at reducing entanglement deaths of cetaceans.